Forms of coerced forgetting as a function of identity change in Kosovo and Metohija - Marjanović, Milica (Sociološki pregled, 2025)
Although numerous social changes taking place during socio-historical development have directly affected family life as a whole, many customs have been maintained and developed into socially acceptable rules of behaviour. In light of such considerations, the main research focus of this paper will be centred on the prism of family relations in the probate proceedings regarding male and female successors, most often siblings. The Law on Inheritance of the Republic of Serbia does not distinguish between male and female successors, that is, the testator’s children who constitute the heirs of the first line of succession; on the other hand, customary law in the tradition of Serbian society dictates that female heirs renounce the inheritance of deceased parents and that the entire property is inherited by the male heir – brother. The successor statement of renunciation of family inheritance is irrevocable. Gender stereotypes are shaped under the strong pressure of social customs and norms, while the main hypothesis of the paper is that tradition and customary law are still stronger than the law, as evidenced by the data from the register of case law. The paper will present the court data from the probate proceedings conducted in the territory of the municipality of Kosovska Mitrovica during 2013 and 2014, confirming the hypothesis that sisters continue to renounce their part of inheritance in favour of brothers, while the reverse situation has been recorded in only 10 cases out of a total of 135 probate proceedings decisions.